Otimização da produção de Goma Xantana: cultivo em biorreator, modelagem e análise de operabilidade - Oliveira, Davi Benedito (Universidade Federal de São Carlos, 2025)
Xanthomonas, a genus of phytopathogenic bacteria, is renowned for producing xanthan gum, a highly viscous biopolymer with diverse industrial applications. Our research group recently engineered a strain that boosts xanthan gum productivity by 50% compared to the wild type. High-viscosity broths often hinder mass transfer and oxygen supply in aerobic cultures. While previous studies have tackled these challenges through advanced aeration and mixing strategies, our approach takes a different path. The hypothesis proposes that the implementation of a controlled continuous cultivation system designed to keep viscosity within an optimal range would ensure unobstructed medium mixing and maintain adequate oxygen transfer. To realize this strategy, a kinetic model was developed capturing biomass growth, product formation, and substrate and oxygen consumption. Existing models from the literature were adapted to fit our experimental data from bench-scale bioreactors. The final model is supported by a neural network trained on our viscosity measurements to predict how viscosity evolves as xanthan gum accumulates. This combined framework supports simulations of batch, fed-batch, and continuous processes, offering versatile tools for process design and optimization. The system was validated with batch cultures in 1.5 L and 6 L bioreactors, and an operability study was conducted under continuous conditions. These experiments identified process parameters that sustain optimal viscosity and maximize oxygen transfer. Ultimately, the approach delivered a 220% productivity increase over standard batch processes, far exceeding initial expectations.
Optimization of Xanthan Gum production: bioreactor cultivation, modeling, and operability analysis
Keywords: Xanthomonas; Cinética; Bioprocessos; Biopolímero; Alta viscosidade; Kinetics; Biopolymer; High viscosity; Bioprocess; ENGENHARIAS::ENGENHARIA BIOMEDICA::BIOENGENHARIA::MODELAGEM DE SISTEMAS BIOLOGICOS; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA